Allergen extracts for immunotherapy in Latin America - Ricardo Cardona-Villa; Andrés Sánchez; Désirée Larenas-Linnemann; Edgardo Járes; Jorge Sánchez (Revista Alergia México, 2018)
Background: The Latin American Society of Allergy, Asthma, and Immunology (SLAAI) presents a document about the use of immunotherapy (IT) in Latin America, where administration patterns, indications and contraindications, effects on health, adverse events and socioeconomic impact are reviewed.